Seeking forgiveness from Haul Mata - Mumbai Archive Project Team (Jio Institute, 2024)
As the rising flames engulf the effigy, prayers are made to Haul Mata, seeking forgiveness for past misgivings and invoking blessings for new beginnings. It is believed that the smoke rising from the burning effigy removes negative forces from the neighbourhood.